SPECIFIC FEATURES OF RUSSIAN MARKET OF INFORMATIONAL TECHNOLOGIES - Daria Yu. Barilo (Вестник Российского экономического университета имени Г. В. Плеханова)
The article provides characteristics of information technologies market, which depend mainly on customers' perception, readiness of partners, market situation and are formed by market participants, large producers of innovation technologies. In line with analyzing the features and restrictions in vendor's work with different audiences (customers, partners) the authors show various tools available for the vendor to shape the market and develop business: training, PR and covering 'success histories' in mass media, product development. Through analyzing specific features of the Russian information technologies market it is possible to propose effective marketing solutions to build the company partnership network functioning on information technologies market. At the same time the research focuses on cloud technologies, the most promising trend of IT market. Using the example of cloud technologies the article discloses the reasons for market specificity and analyzes the ways to optimize solutions connected with partnership network creation. The data of analytical agencies' research give evidence about the shift from the transaction business model to provision of services and product development. It was pointed out that such features of the Russian market as import substitution and introduction of legislative restrictions stipulate quick response and motivate foreign vendors to design and search for new forms of cooperation and priority segments, such as hosting-providers.